PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN KETERAMPILAN MENULIS PARAGRAF DESKRIPSI SISWA KELAS IV SD MUHAMMADIYAH 6 PEKANBARU - Amaliyah, Siti; Kurniaman, Otang; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the low skill of writing paragraph desdcription of fourth grade students of SD Muhammadiyah 6 Pekanbaru, from 22 students, students are categorized as very skilled as many as 2 students, students skilled categorized as much as 5 students, students are quite skilled as much as 2 students, while students are less skilled 13 students. This is research Classroom Action Research (PTK) conducted in 2 cycles each cycle consists of two meetings. This research to improve the skills of writing paragraph description with the use of image media. Data obtained through observation and test. Data analysis technique used is descriptive statistical technique. The results showed that the value of teacher activity achievement in the first cycle percentage score of 66.66%, while in the second cycle percentage score of 91.66%. Student activity in learning also experience improvement, activity of student activity in cycle I percentage score of 66,66% while in cycle II percentage of 91,66%. The result of the skill of writing the description paragraph on an average basic score of 63,22. Meanwhile, the value of the skill of writing the description paragraph on the first cycle score average score of 83.22, then cycle II increases with an average of 85.04. From the results of this study it can be concluded that the use of image media can improve the skills to write paragraph descriptions fourth grade students SD Muhammadiyah 6 Pekanbaru.Keywords: Image Media, Writing Skills Paragraph Description.